2013
DOI: 10.1111/arcm.12032
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectroscopic and Chromaticity Analysis on the Colourative Mechanism of Ancient Goryeo Celadon from GangJin and Buan

Abstract: In ancient Goryeo celadon excavated from the kiln sites in the GangJin and Buan areas, the effect of the chemical composition and ionic state of Fe on the colour was evaluated by Mössbauer spectroscopy and chromaticity analysis. According to chromaticity analysis, the L* value (brightness) of the glaze was shown to be affected more by TiO2 and MnO than by Fe2O3, and the body was affected more by Fe2O3 than by TiO2. The a* value was found to be affected by Fe2O3 and TiO2 in the glaze, whereas there was hardly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This thin layer under the glaze acts as a dark background over which the scattering and absorption of light in the glazes is not affected by the stoneware. The brown colour is attributed to the incorporation of Ti 4+ from the stoneware with the consequent concomitant oxidation of Fe 2+ to Fe 3+ and reduction of Ti 4+ to Ti 3+ (Figure 4.4) (Kim 2001, Jeon 2014. Indeed, in good agreement with this, a recent investigation using Mössbauer spectroscopy has shown that the brown glaze is more oxidised than the blue glaze in Jun ware .…”
Section: Chapter 4 Jun Ware Glaze Colours 41 Introductionsupporting
confidence: 57%
“…This thin layer under the glaze acts as a dark background over which the scattering and absorption of light in the glazes is not affected by the stoneware. The brown colour is attributed to the incorporation of Ti 4+ from the stoneware with the consequent concomitant oxidation of Fe 2+ to Fe 3+ and reduction of Ti 4+ to Ti 3+ (Figure 4.4) (Kim 2001, Jeon 2014. Indeed, in good agreement with this, a recent investigation using Mössbauer spectroscopy has shown that the brown glaze is more oxidised than the blue glaze in Jun ware .…”
Section: Chapter 4 Jun Ware Glaze Colours 41 Introductionsupporting
confidence: 57%
“…Therefore, RS can serve as a viable non-destructive alternative to Mössbauer spectroscopy (which is very slow and expensive) for determining the oxidation state and mineralogy of Fe-bearing phases. 48 Reflectance spectra of the pigments included in this study demonstrate that the spectral dominance of Fe oxyhydroxides generally decreases toward longer wavelengths. Thus, while even small amounts of Fe oxy-hydroxides can dominate the spectral properties below ~1200 nm, at longer wavelengths other phases, such as clays and gypsum can be detected.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, as the sintering temperature is increased in the reducing atmosphere, the whiteness is increased, because Fe 2 O 3 is reduced to FeO. [5][6][7] The whiteness is the lowest when the sintering is completed. When the temperature is continuously increased beyond the sintering point, the whiteness is increased by the appearance of the glass phase.…”
Section: Chromaticitymentioning
confidence: 99%